A new reproducing kernel collocation method for nonlocal fractional boundary value problems with non-smooth solutions. (December 2018) - Li, Xiuying; Wu, Boying
Abstract: In this letter, a new reproducing kernel collocation method is presented for solving nonlocal fractional boundary value problems with non-smooth solutions. The method is based on the reproducing kernel basis function and the polynomial basis function. The present method can avoid finding a reproducing kernel satisfying nonlocal boundary conditions. The effectiveness of the numerical scheme is illustrated through two numerical examples.